Free fire ebook - Box, C. J. (Joe Pickett, 2008)
Don’t miss the JOE PICKETT series—now streaming on Paramount+ Wyoming game warden Joe Pickett hunts a mass murderer in Yellowstone in this thriller from #1 New York Times bestselling author C.J. Box. Joe Pickett’s been hired to investigate one of the most cold-blooded mass killings in Wyoming history. Attorney Clay McCann admitted to slaughtering four campers in a back-country corner of Yellowstone National Park—a “free-fire” zone with no residents or jurisdiction. In this remote fifty-square-mile stretch a man can literally get away with murder. Now McCann’s a free man, and Pickett’s about to discover his motive—one buried in Yellowstone’s rugged terrain, and as dangerous as the man who wants to keep it hidden.